Mortality and Readmission Rates After Heart Failure: A Systematic Review and Meta-Analysis - Lan T; Liao YH; Zhang J; Yang ZP; Xu GS; Zhu L; Fan DM (Dove Medical Press, 2021)
Tian Lan,1,2,* Yan-Hui Liao,3,* Jian Zhang,2 Zhi-Ping Yang,4 Gao-Si Xu,5 Liang Zhu,1 Dai-Ming Fan4 1Department of Health Care Management and Medical Education, The School of Military Preventive Medicine, Air Force Medical University, Xi'an, People's Republic of China; 2Department of Health Care Management, The Second Affiliated Hospital of Nanchang University, Nanchang, People's Republic of China; 3Department of Cardiology, The Second Affiliated Hospital of Nanchang University, Nanchang, People's Republic of China; 4State Key Laboratory of Cancer Biology and National Clinical Research Center for Digestive Diseases, Xijing Hospital of Digestive Diseases, Air Force Medical University, Xi'an, People's Republic of China; 5Department of Nephrology, The Second Affiliated Hospital of Nanchang University, Nanchang, People's Republic of China*These authors contributed equally to this workCorrespondence: Liang Zhu; Dai-Ming Fan Email liangjulia0317@163.com; li20201226@163.comObjective: The current work aimed to examine the rates of and risk factors for mortality and readmission after heart failure (HF).Setting: A systematic search was carried out in PubMed, the Cochrane Library, and EMBASE to identify eligible reports. The random-effects model was utilized to evaluate the pooled results.Participants: A total of 27 studies with 515,238 participants were finally meta-analysed. The HF patients had an average age of 76.3 years, with 51% of the sample being male, in the pooled analysis.Primary and Secondary Outcome Measures: The outcome measures were 30-day and 1-year readmission rates, mortality, and risk factors for readmission and mortality.Results: The effect sizes for readmission and mortality were estimated as the mean and 95% confidence interval (CI). The estimated 30-day and 1-year all-cause readmission rates were 0.19 (95% CI 0.14- 0.23) and 0.53 (95% CI 0.46- 0.59), respectively, while the all-cause mortality rates were 0.14 (95% CI 0.10- 0.18) and 0.29 (95% CI 0.25- 0.33), respectively. Comorbidities were highly prevalent in individuals with HF.Conclusion: Heart failure hospitalization is followed by high readmission and mortality rates.Keywords: heart failure, meta-analysis, prevalence, readmission, mortality, hospitalization